Power meter principles for optimizing testing, training, and performance strategies in cycling - Broeder, C. E. (Routledge handbook of ergonomics in sport and exercise, 2016)
Cycling requires a wide array of physiological, biochemical, mechanical, psychological and strategic needs. For all cyclists, there are four main external forces that either work with or against a cyclist, including gravity, air resistance, friction and rolling resistance (Glaskin, 2012). How these external forces affect a given ride or race are determined by moment-to-moment ride condition factors. These factors include road gradient, wind intensity and direction, the cyclist`s current aerodynamic position and the rider`s ability to harness neuromuscular power at the time force is needed to alter inertia (Glaskin, 2012). Also, other physiological factors, including muscle glycogen stores at the moment force is needed, thermoregulatory effects on the cardiovascular system, the central governor and psychological factors, play major roles in how well a cyclist can overcome a negative external force (Coyle, 1999; Coyle et al., 1988; Gollnick et al., 1973; Noakes et al., 2001; St Clair Gibson et al., 2001). How these factors impact the actual physiological ride stress is also determined by a rider`s anthropometric profile such as current body weight and upper to lower body lean tissue distribution (Martin, 2012), or the cyclist`s current condition level (i.e. lactate or functional threshold and maximal aerobic capacity) (Allen and Coggan, 2010; Bentley et al., 2001; Hawley and Noakes, 1992). These factors, along with the effects exerted by other riders (i.e. drafting or breakaway attempts) for a given race event, determines the final imposed physiological and perceived stressors of a given event.